2018
DOI: 10.1002/ajpa.23435
|View full text |Cite
|
Sign up to set email alerts
|

Handedness in gestural and manipulative actions in male hunter‐gatherer Aka pygmies from Central African Republic

Abstract: Although we do not intend to assume generalizable results due to our reduced sample, our observations provide additional information on handedness in a contemporary traditional society. Especially, the study mainly evidenced considerable cultural effects in gestures while also supporting theories considering active tool manipulation as one of the overriding factor in human handedness evolution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 80 publications
0
11
0
Order By: Relevance
“…Previous studies on the subject of lateralization in humans (past and modern) are not entirely on agreement on what expectations might be. Modern populations exhibit footedness (Gabbard 1996;Gentry & Gabbard 1995) and handedness (Stock et al 2013) but extant hunter-gatherers only exhibit handedness during activities involving complex tasks (Cavanagh et al 2016;Hurtado et al 1985;Robira et al 2018) and footedness has not been studied. Even though hunter-gatherers have been studied in terms of gait and locomotion (Fredericks et al 2015;Hatala et al 2013Pontzer, 2014Lieberman et al 2010;Niemitz 2010;Pontzer et al 2014), studies on modern populations indicate that the influence of walking gait on footedness is not significant (Zverev 2006).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies on the subject of lateralization in humans (past and modern) are not entirely on agreement on what expectations might be. Modern populations exhibit footedness (Gabbard 1996;Gentry & Gabbard 1995) and handedness (Stock et al 2013) but extant hunter-gatherers only exhibit handedness during activities involving complex tasks (Cavanagh et al 2016;Hurtado et al 1985;Robira et al 2018) and footedness has not been studied. Even though hunter-gatherers have been studied in terms of gait and locomotion (Fredericks et al 2015;Hatala et al 2013Pontzer, 2014Lieberman et al 2010;Niemitz 2010;Pontzer et al 2014), studies on modern populations indicate that the influence of walking gait on footedness is not significant (Zverev 2006).…”
Section: Resultsmentioning
confidence: 99%
“…Finally, we were interested in whether the carpal bones reflected the shared load model (Hamlin 2001) or if it reflected a partially shared load with greater female burden (Wentz 2006;Wentz 2010). We used an index variable for four carpal bones to examine differences in activity (shared workload or sex-based division of labor) (Cavanagh et al 2016;Robira et al 2018). Again, the tests were underpowered due to small sample sizes and female samples were smaller than male samples.…”
Section: Resultsmentioning
confidence: 99%
“…Bias against left handedness continues to be a topical issue as most tools designed have a right handed bias. Other studies have supported cultural effects in gestures and active tool manipulation as one of the overriding factor in human handedness evolution [34].…”
Section: Discussionmentioning
confidence: 96%
“…In naturalistic settings like these, pointing may in fact be the most commonly used gesture type of all, more common than depictive gestures or conventional emblems like the "thumbs up." One group of researchers filmed 25 Aka men in the Central African Republic who were gathered to cook and socialize, and found that pointing accounted for more than 60% of their gestures (Robira et al, 2018). Similarly, Alibali et al (2011) examined math lectures in the United States and Japan and found that attention-directing movements-chiefly pointing, but also other forms of indicating-accounted for more than 60% of gestures.…”
Section: A Communicative Workhorsementioning
confidence: 99%